The Lexicons Used in Palawakya Dance Costumes - Anita Sofia Veronia; I Gede Budasi; Dewa Putu Ramendra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Palawakya dance is a kind of dance which mixes the arts of dance, music, and old Balinese song called Kakawin. Culturally, the dance consists of various lexicons used in common life but it is getting rarely used by people nowadays. This research was designed in the form of descriptive qualitative research by applying an ecolinguistic approach. It was focused on analyzing the lexicons of Palawakya dance costumes in Jagaraga Village, Singaraja. Observation and interview were conducted to obtain the data of this research by involving three informants. The informants were selected by using purposive sampling. The instruments used in gaining the data were observation sheet and interview guide. The results of this study showed that there were 17 lexicons found in the dance costumes. The dance costumes were divided into five parts; 1) head costume consists of five lexicons, 2) neck costume consists of one lexicon, 3) body costume consists of eight lexicons, 4) hands, costume consists of one lexicon, 5) leg costume consists of two lexicons. In addition, another result revealed that there were 16 cultural meanings found in the Palawakya dance costumes. Keywords : Costume, Cultural Meaning, Ecolinguistics, lexicons, Palawakya